Meta-Analysis: Effects of Gender, Waiting Time, Visits, and Insurance on Outpatient Satisfaction with Health Services - Prasetyowati, Regita Azzahra; Ibrahim, Natalia Prisca; Arini, Septa Santiya; Murti, Bhisma; Munawaroh, Siti Mar'atul (Journal of Health Policy and Management, 2025)
Background: Patient satisfaction is the result of the service process felt by the patient, overall satisfaction arises from the patient's evaluation of the experience or as an interaction, including the availability of health services provided by officers (health workers), so that patient satisfaction can be used to assess the quality of services received by the patient. This study aims to estimate the magnitude of the influence of gender, waiting time, visits, and insurance on health service satisfaction. Subjects and Method: Systematic review and meta-analysis using PRISMA flow charts and PICO models. Population: outpatients. Intervention: Female, long waiting time, already visited, using insurance. Comparison: Male, short waiting time, first time visit, and not using insurance. Outcome: Outpatient satisfaction with health services. The online databases used were Google Scholar, Biomedcentral, Taylor & Francis and Plos with the keywords gender, waiting time, visits, insurance, outpatient satisfaction, cross-sectional and aOR. Inclusion criteria were full text articles with cross-sectional use of multivariate analysis that included aOR and were published from 2014-2024. Data analysis using the RevMan 5.3 application. Result: Twelve primary studies were used to analyze gender and patient satisfaction with health services. Women had satisfaction with health services 1.19 times compared to men (aOR= 1.19; 95% CI=1.11 to 1.28; p<0.001). Ten primary studies were used to analyze insurance and patient satisfaction with health services. Patients who have insurance are 1.23 times more satisfied with health services than those who do not have insurance (aOR= 1.23; 95% CI=1.09 to 1.40; p<0.001). Seven primary studies were used to analyze waiting times and patient satisfaction with health services. Patients who experienced short waiting times were 0.30 times more satisfied with health services compared to those with long waiting times (aOR=0.30; 95% CI=0.21 to 0.44; p<0.001). Seven primary studies were used to analyze visit frequency and patient satisfaction with health services. Patients who have visited are 2.96 times more satisfied with health services than patients who are visiting for the first time (aOR=2.96; 95% CI=2.60 to 3.37; p<0.001). Conclusion: Female gender, short waiting times, repeat visits and insurance in increasing outpatient satisfaction with health services.